A práxis política da Igreja Católica na Diocese de Chapecó/SC (1970 e 1980) - Silva, Tiago Arcego da (2017)
From the end of World War II a new kind of development is forced to the Latin American continent. In this context, different movements of resistance and struggle for rights coming up. At the same time, into ecclesial field, the opening proposed by the Vatican Council II (1962-1965) and by Medellin’s (1968) and Puebla’s (1979) Episcopal Conferences, will support the birth and elaboration of Liberation Theology, created at that time as a proposal to superate inequalities in the continent, that should be protoganized by the impoverished people. Its praxis leads to different confrotations, conflicts and opositions. However, the impacts felt in the new proposal of organization of the Catholic Church in whole continent will find pecualiarities and similarities in each place. In this way, this paper wants to analise the Catholic Church’s politics praxis at Chapecó, from the discuss around the Liberation Theology to the local reality, looking at its organization and the mainly conflicts that happened in 1970s and 1980s. All this advance, practical and theoretical of Liberation Theology, happens at the same time as Bishop Dom José Gomes arrivals into Diocese of Chapecó; he has an important participation in this new theological and pastoral proposal. The attitudes of Catholic Church will be influential to the history of the region, especially when it refers to the social conflicts of great repercussion, such as cases of Indigenous Land Demarcations of Toldo Xapexó (1978) and Toldo Chimbangue (1974-1985), the case of African Swine Fever (1978), the case of Hydroelectric Plant building at Itá (1979-1985) and the case of Farm Burro Branco ocupation, at Campo Erê (1980). In this way, it is noticed a political praxis consolidated in a movement that had a lot of strongness within the Catholic Church in whole Latin American continent, in 1970s and 1980s, which had been translated into a specific reality in such a way that it was decisive to the regional development.